Errors in solving quadratic equations and their impact on secondary school students' mathematics performance: A case study in Lebowakgomo sub-district - Mathonsi, Violet; Rankhumise, Mmushetji Petrus (Indonesian Journal of Science and Mathematics Education, 2025)
Errors in solving quadratic equations are common among high school students and can significantly impact their mathematical proficiency. This study aimed to investigate the types of errors made by Grade 10 students and identify the factors contributing to these errors. The study was conducted in three senior secondary schools in Lebowakgomo District, Limpopo Province, involving ninety-nine Mathematics students, with nine selected for interviews. Data were analyzed quantitatively through students’ test scores and qualitatively using document analysis and interviews. The findings revealed that students’ difficulties were often reflected in errors related to carelessness, misapplication of numerical operations, order of operations, and challenges in handling algebraic equations. These conceptual and procedural inconsistencies hinder students' problem-solving abilities. The implication of this study is the urgent need for targeted instructional strategies that address conceptual understanding and procedural fluency to improve students' academic performance in Mathematics.